KERJASAMA SISTER CITY PEMERINTAH KOTA BANDUNG (INDONESIA) DAN PEMERINTAH KOTA PETALING JAYA (MALAYSIA) DALAM MENINGKATKAN INDUSTRI EKONOMI KREATIF BANDUNG TAHUN 2012-2016 - Mariane Olivia Delanova; Meizania Vania Utami Effendi; Yuswari Octonain Djemat (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
In accordance with Law no.37 of 1999 on foreign relations and law no.32 of 2004 on regional government further strengthen the position of local government to conduct an external relationship in an effort to build its own region. The purpose of this study is to describe more deeply about the cooperation of sister city Bandung city government in improving the creative economy industry in Bandung City and Petaling Jaya City, Malaysia with the program "Little Bandung" owned by the government of Bandung. In order to face the existence of ASEAN Economic Community (MEA). This study uses the approach of liberalism, the concept of creative economy, sister city, paradiplomasi and the theory of international cooperation. So as to illustrate the process of foreign cooperation implemented by the Government of Bandung. This research is descriptive and data collection technique through interview and literature study. In this study it can be concluded that with the existence of law no.37 of 1999 on foreign relations and law no.32 of 2004 on local government, a benchmark on each local government to build and develop its own region through an outside relationship Country in the form of cooperation among local governments apart from the central government.